Evaluation of nine forms of metabolic syndrome diagnosis as risk for cardiovascular disease: An analysis of isolated and combined metabolic factors - Orihuela Manrique, Eder Jesus (2024)
Background: Metabolic syndrome (MetS) is a pathological condition varying according to the guidelines used, leading to ongoing debate on whether all these forms of defining MetS offer the same level of risk for developing cardiovascular diseases (CVDs). The aim of the study was: 1) to determine the prevalence of each type of MetS; 2) to assess the association of each type with CVDs over a 5-year follow-up period; and 3) to analyze whether each possible combination of MetS carries the same level of risk for developing CVD in the time above frame. Methods: This study is a secondary analysis of a Peruvian cohort database. The dependent variable was the development of CVD. In contrast, the independent variable was MetS, defined based on nine diagnostic methods: Adult Treatment Panel III (ATPIII), International Diabetes Federation (IDF), World Health Organization (WHO), Joint Interim Statement (JIS), European Group for the Study of Insulin Resistance (EGIR), American Heart Association and National Heart, Lung, and Blood Institute (AHA/NHLBI), American Association of Clinical Endocrinologists (AACE), Latin American Diabetes Association (ALAD), and International Lipid Information Bureau Latin America (ILIBLA). Results were presented as relative risk (RR). Results: The overall prevalence of MetS was 40.59%, while the 5-year incidence of CVD was 1.69%. The lowest prevalence was found with ALAD criteria (5.6%), while the highest was ILIBLA (37%). Diagnostic forms of MetS according to ILIBLA (RR = 5.06; 95% confidence interval (CI): 1.64 - 15.62), AHA/NHLBI (RR = 5.06; 95% CI: 1.64 - 15.62), JIS (RR = 3.66; 95% CI: 1.22 - 10.97), and API (RR = 2.83; 95% CI: 1.11 - 7.20) showed a risk of CVD. Additionally, hyperglycemia, hypertriglyceridemia, and elevated blood pressure were found to be individually associated with the presence of CVD. In contrast, other factors, such as altered waist circumference (WC) and low high-density lipoprotein (HDL), are only associated with an increased risk in combination with other markers.